Determinants of Personal Taxpayer's Compliance Level (Empirical Study at the Jakarta Cilandak Primary Tax Service Office) - Rinaldo, Rinaldo; Purwanto, Edi (Mahesa Research Center, 2022)
This study was conducted to determine the impact of understanding the electronic accounting system, system quality, penalties, and gender on the level of tax obligations of individual taxpayers. The inspection site will be at the Pratama Jakarta Cilandak Tax Office. This survey is a quantitative survey using a primary data source in the form of a questionnaire. This survey data collection method used a random sampling technique with a sample of 100 respondents. A method of data analysis using multiple linear regression analysis in the program SPSS22.0 These results show that, among other things, understanding of electronic billing systems, system quality, and tax penalties have a significant impact, while gender variables do not significantly affect the degree of compliance by individual taxpayers. I am. The results of the simultaneous investigation show that an individual's understanding of the electronic accounting system, system quality, tax penalties, and gender can have a significant impact on an individual's tax compliance.